A new species of Lobulia (Squamata: Scincidae) from Papua New Guinea - Kraus, Fred (Zootaxa, 2020)
I describe a new skink of the genus Lobulia from Mt. Simpson in southeasternmost New Guinea. This species differs from all other members of the genus in having only three pairs of enlarged chin shields and only the first pair in medial contact. It is most similar in scalation to L. elegans but is readily distinguished from that species by its color pattern, body size and shape, and numbers of lamellae. Morphological data on L. elegans have not been reported since the description of the holotype in 1897, so I provide a redescription of that species based on six specimens—including the holotype—of certain conspecificity and from within approximately 100 km of the type locality at Mt. Victoria. I also elevate Lygosoma elegantoides lobulus from synonymy with Lobulia elegans, from which it is readily distinguished on the basis of scalational and color-pattern features. The resurrected L. lobulus and the new species from Mt. Simpson represent the seventh and eighth recognized species of Lobulia, and the Mt. Simpson species is the fifth member of the Papuan herpetofauna that is apparently endemic to Mt. Simpson. Mt. Simpson appears to be a moderate center of local endemism within southeastern New Guinea.